A commentary on transdermal drug delivery systems in clinical trials. Issue 9 (6th March 2013) - Watkinson, Adam C.; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract The number of drugs available as marketed transdermal products is limited to those that exhibit the correct physicochemical and pharmacokinetic properties that enable their effective delivery across the skin. In this respect, there are less than 20 drugs that are currently marketed in the US and EU as products that deliver systemic levels of their active ingredients. An analysis of clinical trials conducted in the transdermal sector shows a similar picture with only nine drugs accounting for approximately 80% of all transdermal clinical trials listed on ClinicalTrials.gov. Those drugs for which there are very few transdermal trials listed consist mostly of molecules that are inherently unsuitable for transdermal delivery and serve as a clear warning to drug developers that the science that governs transdermal drug delivery is well reflected by the successes and failures of drugs in development as well as those that make it to the market. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3082–3088, 2013